The relationship between young females' attitudes toward premarital sex and their interpersonal and personality characteristics. - Ocbena, Michelle; Ramos, Chresly M. (Miag-ao, Iloilo University of the Philippines in the Visayas, Division of Social Sciences, 2008)
The study was undertaken to know the relationship between young females' attitudes toward premarital sex and their personality and interpersonal characteristics. It generally aims to determine if there is a relationship between the young females' general attitude towards premarital sex and the personality and interpersonal factors such as level of self-esteem, type of, personality, degree of susceptibility to peer pressure, and level of parent-adolescent communication. The sample of this study is fifty-three unmarried female students with ages ranging from nineteen to twenty-four. The study reveals that majority of those who have high self-esteem ; those who are extraverts ; those who have high level of communication with their parents ; and those who are susceptible to peer pressure have negative attitudes toward premarital sex.
Research Project (Undergraduate, Bachelor of Arts in Sociology) College of Arts and Sciences, University of the Philippines in the Visayas.
Keywords: Premarital sex